Inpatient charges among HIV/AIDS patients in Rhode Island from 2000-2004 - Fabio Anthony; Barbour Kamil E; Pearlman Deborah N (BMC, 2009)
Abstract Background Inpatient HIV/AIDS charges decreased from 1996-2000. This decrease was mainly attributable to treatment of HIV/AIDS patients with Highly Active Antiretroviral Therapy (HAART). This study aims to evaluate the trend in inpatient charges from 2000-2004. Methods Rhode Island Hospital Discharge Data (HDD) from 2000 to 2004 was used. International Classification of Disease (ICD-9) diagnosis code 042-044 was used to identify HIV/AIDS admissions. The final study population included 1927 HIV/AIDS discharges. We used a multivariable linear regression model to examine the factors associated with inflation adjusted inpatient charges. Results We found a significant increase in inpatient charges from 2000-2004 after adjusting for length of stay (LOS), gender, age, race and point of entry for hospitalization. In addition to calendar year, LOS, gender and race were also associated with inpatient charges. Conclusion HIV/AIDS inpatient charges increased after adjusting for inflation despite earlier studies that showed a decline. Our results have implications for uninsured, as well as insured HIV/AIDS patients who do not have a medical plan that covers their charges sufficiently. Future research should investigate what factors are contributing to rising inpatient charges among HIV/AIDS patients.